Life cycle assessment of cotton woven shirts and alternative manufacturing techniques - KERÇ, ASLIHAN; AKGÜL, DENİZ (SPRINGER, 2020)
In this study, the life cycle assessment of cotton woven shirt production, from cotton cultivation to the final product, has been done. In this scope, four alternative production scenarios were developed and evaluated with GaBi 8.0 software with CML 2001-January 2016 methodology. These scenarios include conventional cotton woven shirt production, organic cotton cultivation incorporated with renewable energy use in production phase, evaluation of natural dyeing in manufacturing process and using recovered cotton as the raw material. For each of these scenarios, several environmental impact categories including global warming, acidification and eutrophication potentials were evaluated. The functional unit was determined as 1000 pcs of shirts. In the assessment of conventional cotton woven shirt production, pesticide and synthetic fertilizer usage during cotton cultivation as well as the energy supply for the production phases were found to be the major factors increasing environmental impacts. Using organic cotton cultivation and renewable energy sources instead of the traditional techniques, decreased eutrophication potential, acidification potential and global warming potential by 48%, 52% and 70%, respectively. Using recovered cotton fibers as the raw material decreased eutrophication potential, acidification potential, abiotic depletion potential and global warming potential by 96%, 90%, 69% and 47%, respectively, by eliminating the environmental impacts that originate from cotton cultivation stage. Moreover, as these recovered cotton fibers are already colored, additional dyeing is not required. Alternatively, natural dyeing process could be a good alternative to synthetic dyeing and decline environmental impacts by minimizing the use of chemicals and decreasing the required heat for dyeing. Graphic abstract
Keywords: Cotton; Environmental impact; Life cycle assessment; Organic agriculture; Sustainability; Textile; GREENHOUSE-GAS EMISSIONS; ENVIRONMENTAL-IMPACT; WATER FOOTPRINT; SUSTAINABILITY; PRODUCTS; FERTILIZATION; EFFICIENCY; FRAMEWORK; SYSTEMS; LCA